Peran Persepsi Nilai Yang Dirasakan Konsumen dalam Memediasi Pengaruh Kualitas Produk, dan Persepsi Harga terhadap Kepuasan Konsumen Generasi Z Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang (Studi Pada Rucas Brand) - Khosibul Anam; Agus Widarko; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The rapid development of the local fashion industry in Indonesia has intensified competition among brands, particularly in attracting Generation Z consumers. Consumer satisfaction is a key determinant of brand sustainability and is influenced by product quality, price perception, and perceived value. This study aims to examine the effect of product quality and price perception on Generation Z consumer satisfaction, with perceived value as a mediating variable, using Rucas as the research object. This research adopts a quantitative explanatory approach. The population consists of students of the Faculty of Economics and Business, Universitas Islam Malang, who have purchased or used Rucas products. A total of 100 respondents were selected using purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results show that product quality and price perception have a positive and significant effect on consumer satisfaction. Product quality and price perception also significantly affect perceived value. Furthermore, perceived value has a positive and significant effect on consumer satisfaction and mediates the relationship between product quality and consumer satisfaction, but does not mediate the relationship between price perception and consumer satisfaction. These findings highlight the important role of perceived value in strengthening the influence of product quality on Generation Z consumer satisfaction in local fashion brands. Keywords: Product Quality, Price Perception, Perceived Value, Consumer Satisfaction, Generation Z